EDUKASI HAK ATAS PANGAN MELALUI KEGIATAN WORLD FOOD DAY 2025 DI BOGOR - Rohmat, Abdul; Dessy Trihastuti,; Joko Tri Hartadi,; Suroto,; Septian Alan Nuwaryanto, (Jurnal Pengabdian Teratai, 2025)
This community engagement activity aimed to strengthen public awareness of the right to food and promote sustainable food systems through the commemoration of World Food Day 2025 in Bogor. The program was designed using a participatory approach involving students, local government, food-related institutions, and small and medium enterprises (UMKM). The implementation methods included educational seminars on food security, exhibitions of local food products, cooking competitions, community campaigns, and direct interaction with stakeholders to encourage consumption of diverse, nutritious, and safe foods. The activities successfully attracted approximately 150 participants and demonstrated increased understanding of food rights, sustainable nutrition practices, and the importance of supporting local food-based innovation. The event also facilitated collaboration among students, policymakers, and UMKM, resulting in greater community involvement in promoting responsible food consumption and reducing food waste. The outcomes indicate that structured educational interventions and multisector collaboration can effectively enhance community literacy on food security issues. The implications of this activity highlight the need for continuous public education programs, strengthened university–community partnerships, and expanded support for local food producers to sustain long-term food resilience.